The NLRP3 inflammasome and the emerging role of colchicine to inhibit atherosclerosis-associated inflammation - Martínez, Gonzalo J.; Celermajer, David S.; Patel, Sanjay (Atherosclerosis, 2018)
Atherosclerosis is considered a chronic inflammatory disease of the arterial wall. Recently, compelling evidence has arisen for the role of monocytes and neutrophils and a particular protein complex that resides within these cells – the NLRP3 inflammasome – in atherosclerosis-associated inflammation. It is now also known that cholesterol crystals are present through all stages of atherosclerosis and can activate the NLRP3 inflammasome within these inflammatory cells to produce interleukin 1β and interleukin 18 – key mediators in the inflammatory cascade that drive plaque progression and instability. In this review, we describe the role of monocytes/macrophages and neutrophils in atherosclerosis, outline mechanisms of activation of the NLRP3 inflammasome in the setting of atherosclerosis-associated inflammation and discuss potential therapies that specifically target the NLRP3 inflammasome and/or its downstream mediators in atherosclerosis, with a particular focus on the emerging role of colchicine. •The NLRP3 inflammasome leads to IL-1β (and IL-18) production.•IL-1β promotes atherosclerotic plaque development and destabilization.•Colchicine can block the NLRP3 inflammasome and thus IL-1β production.•Data suggest a favourable effect of colchicine on atherosclerosis-associated inflammation.•On going trials seek to clarify the role of colchicine in patients with atherosclerosis.